VD_FINDINFO HC / 2009 / 445 vom 2. November 2009 - VD Tribunal cantonal (2009)
CONTRAT DE TRAVAIL, COMPÉTENCE, CONVENTION D'ARBITRAGE, DROIT IMPÉRATIF, ARBITRABILITÉ | 5 C-Arb, 341 al. 1 CO, 452 al. 1ter CPC, 60 CPC, 1 al. 1 LFors, 24 LFors